Matching Allocation Problems with Endogenous Information Acquisition - Sophie Bade (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
The paper introduces the assumption of costly information acquisition to the theory of mechanism design for matching allocation problems. It is shown that the assumption of endogenous information acquisition greatly changes some of the cherished results in that theory: in particular, the first-best might not be implementable. Moreover, it might not even be possible to implement the second-best through trade. In addition, the paper highlights the use of randomness in setting incentives for efficient learning. The trade-offs among simultaneous and sequential learning and among efficient learning and efficient allocations are discussed.
Keywords: C78; C70; D50; 330; Serial Dictatorship; House Allocation Problems; Endogenous Information